Was will die Karl-Rahner-Gesamtausgabe? - Raffelt, Albert (Zeitschrift für katholische Theologie, 1999)
Karl Rahner's „Sämtliche Werke“ (1995–) is the first edition of the complete works of a German-language catholic theologican. The work of Karl Rahner consists of about 1.500 titles (over 4.000 bibliographical items, including reprints and translations), and so is not easy to assess. Parts of the work have not been published before (e.g. lectures, his theological dissertation). Many articles had their origin in specific historical occasions (the definition of the Assumptio, II. Vatican Council etc.). These data and the importance of Rahner's work for the catholic theology of the 20th century in general are sufficient reasons for a new edition. The arrangement is chronological, but within the periods of the work the thematical units are combined and collected. Six volumes (of 32) have been published up to 1999. All published versions of the works of Karl Rahner will also be available in electronic form at the Karl-Rahner-Archiv Innsbruck (pdf-files) as an addition to the book edition and as a first step to a future complete Karl-Rahner-database. The combination of the traditional and the digital edition is meant as a critical-historical edition for the time being.